Green approach towards size controlled synthesis of biocompatible antibacterial metal nanoparticles in aqueous phase using lysozyme - Kumar, Umesh; Ranjan, Amaresh K.; Sharan, Chandrashekhar; Hardikar, Anandwardhan A.; Pundle, Archana; Poddar, Pankaj (Current Nanoscience, 2012)
Inspired by array of proteins present in nature, we choose lysozyme (hen egg protein) as a model system to synthesize nanoparticles of noble metals to understand the mechanism of interaction as well as to use them for potential applications such as potent antibacterial agents. Lysozyme is a very well studied biomolecule containing aromatic amino acids like tryptophan and tyrosine. Tyrosine has phenoxy group which is considered to be responsible for interacting with the metal ions. Lysozyme can be suitably modified by treatment with N-bromosuccinimide/N-acetylimidazole to obtain tight control over size distribution of nanoparticles. Here we report the direct synthesis of nanocrystals of gold and silver at controlled pH and light conditions without using any known reducing agents. Out of these, synthesis of gold nanoparticles is assisted by the presence of low concentration of Ag+ ions through the galvanic exchange. It is remarkable to note that the structure of protein is not changed drastically as seen by the FTIR studies. As-synthesized lysozyme capped nanoparticles prepared by this method are biocompatible and retain antibacterial property.
Keywords: Antibacterial; Biocompatible; Gold; lysozyme; Nanoparticles; Silver

Growth of oriented single crystalline La-doped TiO2 nanorod arrays electrode and investigation of optoelectronic properties for enhanced photoelectrochemical activity - Sadhu, Subha; Poddar, Pankaj (RSC Advances, 2013)
Fabrication of single crystalline, oriented one-dimensional (1D) rods or wires of titania on transparent conducting oxide (TCO) substrates have enormous significance in the area of photoelectrochemical research owning to their unique optoelectronic properties. It is possible to modify the electrical conductivity and optoelectronic properties of titania by intentional inclusion of atomic impurity in the material. Here for the first time, we have doped lanthanum homogeneously in TiO2 nanorod arrays. The homogeneous distribution of lanthanum in titania lattice is confirmed by scanning transmission electron microscopy (STEM) elemental mapping and line scanning analysis. After doping with lanthanum, there is a negative shift of the flat-band potential of the TiO2 nanorods and the charge carrier density of the nanorods is also improved. The energy-conversion efficiency of a dye-sensitized solar cell based on 4 mol% La-doped nanorods is increased about 21% compared with the undoped one.

Growth of flower-like patterns of TiO2 nanorods over FTO substrate - Issar, Sheetal; Poddar, Pankaj; Mehra, N. C.; Mahapatro, Ajit K. (International Conference on Technologically Advanced Materials (ICTAM), 2017)
Nanostructures such as nanoparticles, nanowires, nanorods, nanotubes have attracted great interest with the understanding of shape and size dependence in the electronic and sensing properties. This work demonstrates growth and characterization of one-dimensional nanorods of titanium-dioxide (TiO2) on the fluorine doped tin oxide (FTO) substrate by using hydrothermal method. Field effect scanning electron microscopy shows flower-like morphology, and energy-dispersive X-ray spectroscopy confirms the presence of Ti and O. The X-ray diffraction peaks agree well with the JCPDS data. Initially, the 1D nanorods are formed and high concentration of precursor assists evolution of the short branches to form flower-like structures.